Ileocecal Fistula Caused by Multiple Foreign Magnetic Bodies Ingestion - Vittorio Cherchi; Gian Luigi Adani; Elda Righi; Umberto Baccarani; Giovanni Terrosu; Nicola Vernaccini; Vittorio Bresadola; Sergio Intini; Andrea Risaliti (Case Reports in Surgery)
The incidence of accidental foreign body (FBs) ingestion is 100,000 cases/year in the US, with over than 80% of cases occurring in children below 5 years of age. Although a single FB may pass spontaneously and uneventfully through the digestive tract, the ingestion of multiple magnetics can cause serious morbidity due to proximate attraction through the intestinal wall. Morbidity and mortality depend on a prompt and correct diagnosis which is often difficult and delayed due to the patient's age and because the accidental ingestion may go unnoticed. We report our experience in the treatment of an 11-year-old child who presented to the emergency department with increasing abdominal pain, vomiting, diarrhea, and fever. Surgery evidenced an ileocecal fistula secondary to multiple magnetic FB ingestion with attraction by both sides of the intestinal wall. A 5-centimeter ileal resection was performed, and the cecal fistula was closed with a longitudinal manual suture. The child was discharged at postoperative day 8. After one year, the patient’s clinical condition was good.